Poverty among migrant, mixed, and non-migrant households: the role of non-teleworkability and single-earnership in Germany - Maria Hornung; Emanuela Stuffolino; Hannah Zagel (Journal of Ethnic and Migration Studies, 2024)
Migrant and mixed households have higher poverty than non-migrant households. This is partly because single-earner two-adult households are more prevalent in migrant and mixed households and because such households have different job characteristics. One crucial job characteristic is teleworkability. Whether or not individuals can work from home has become a dividing factor in the labour market. While much research has focused on how teleworkability affects poverty in the majority population, less attention has been devoted to migrant and mixed two-adult households. Using the German Microcensus (2019), we construct work arrangements based on the number of earners in the household and their job`s teleworkability to predict poverty for non-migrant (N0.167em=0.167em49,507), mixed (N0.167em=0.167em6,818), and migrant households (N0.167em=0.167em8,922). Descriptive statistics show that, in Germany, migrant and mixed households have more single-earner and non-teleworkable work arrangements. Results from logistic regressions report higher poverty for non-teleworkable and single-earner work arrangements, putting mixed and migrant households at an increased disadvantage. Furthermore, we find that migrant (and mixed) households not only have a higher prevalence of high-poverty work arrangements but also higher poverty than non-migrant and mixed households within the same work arrangements.
Keywords: 320; Teleworkability; labour market; poverty; mixed households; migration